Higher education staff development: a need-oriented approach based on survey research - Klaudia Zwolińska-Glądys; Sylwia Lorenc; Natalia Kowalska; Radosław Pomykała (Scientific Reports)
Abstract Continuous professional development of university employees is crucial to implementing the mission of higher education institutions. University staff work includes various activities related to teaching, research studies, and cooperation with the industrial sector. It motivated authors to identify crucial areas and skills that should be developed at the academic level. Higher education institutions in Poland were used as a case study. An analysis of the training needs of teaching and research staff was conducted. The study aimed to assess the approach and perspective of academic teachers to training initiatives. A survey with questions about the importance of developing employees’ skills in a given area was used as a research tool. The paper identified the main fields that, according to employees, should be developed through additional specialist training. The results indicate that the gender and age of respondents may influence the answers given.